The Impact of the ACA's Extension of Coverage to Dependents on Young Adults' Access to Care and Prescription Drugs. (15th February 2016) - Amuedo‐Dorantes, Catalina; Yaya, Mehmet E.
Abstract : We examine the impact of the Affordable Care Act (ACA)'s extension of coverage to dependents on young adults' access to care as captured by their likelihood of delaying needed medical care or forgoing prescription drugs. Using data from the 2002 through 2013 waves of the National Health Interview Survey, we find that the federal mandate has not only significantly lowered their likelihood of being uninsured, but also significantly reduced their likelihood of delaying needed medical care or forgoing prescription drugs by 13% and by 31%, respectively. Because these early impacts might still underestimate the long‐run effect of greater health insurance coverage on health care utilization, the findings hint on the success of the ACA's expansion of dependent coverage to young adults in improving their access to health care.